PENGARUH KUALITAS AUDITOR, LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS TERHADAP OPINI AUDIT GOING CONCERN PADA SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Pasaribu, Aria Masdiana (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2015)
This research is aimed to emprirically examines the influences of auditor quality, liquidity, solvability andprofitability to the Going Concern Auditing Opinion (GCAO). This research?s populations are16 companies from sub sektor food and drink companies listed in Bursa Efek Indonesia (BEI) for the year 2011, 2012, and 2013. Thisresearch samples were 15 companies or 45 observation data which had close by purposive sampling. The data whichused is secondary data that acquired from Bursa Efek Indonesia and it was analyzed by logistic regression. Theresult showed that the auditor quality, liquidity and profitability have no significant influence to the going concernopinion. Whereas the solvability have signifcant influence to the going concern opinion